Improving micro-grid management: A review of integration of supercapacitor across different operating modes - Mohamed El-Sayed M. Essa; Mohammed Fouad Ali; Elwy E. El-kholy; Mohammed Amer; Mahmoud Elsisi; Uzair Sajjad; Khalid Hamid; Hilmy El-sayed Awad (Heliyon)
The field of electrical energy is moving through many rapid changes and continuous development, especially with the huge boom in the field of artificial intelligence (AI) and the presence of renewable energy systems (RESs). Simultaneously with this development, it was necessary to have energy storage systems such as super capacitors and batteries. This necessity increased with sudden changes in climate or loads that affect the output of generation systems such as solar and wind energy systems. The main goal of this study is to focus on supercapacitors as a future solution with high reliability. It studies all the various factors and operational modes such as the principle of operation, installation, types and modeling of supercapacitors. The study also focused on the employment of supercapacitors in diverse applications, especially in microgrids with their various systems including control and energy management strategies for these systems and investigating the integration between AI, supercapacitors and microgrids and the outcome of this integration. Besides, this research intends to a proposal for a hybrid energy storage systems (HESS) suitable for different loads, including solar cells as main source with supercapacitors and batteries. In addition, it proposes the energy management system (EMS) as well as appropriate control system, to solve the problems of utilities and microgrids and meet the power demand of loads for different operating conditions.